Benzo[a]pyrene-induced changes in carboxylesterase, acetylcholinesterase and heat shock protein 70 of Lymantria dispar (Lepidoptera: Lymantriidae) from unpolluted and polluted forests - Grčić, Anja; Ilijin, Larisa; Mrdaković, Marija; Vlahović, Milena; Filipović, Aleksandra; Đurašević, Siniša; Perić-Mataruga, Vesna (Archives of Biological Sciences, 2019)
Paper description: Anthropogenic activities are responsible for increased concentrations of the pollutant benzo[a]pyrene in the environment. Identifying molecular indicators of stress induced by benzo[a]pyrene in a widespread insect species, Lymantria dispar has great importance in pollution biomonitoring. Two populations of Lymantria dispar larvae from different habitats were fed on benzo[a]pyrene. Carboxylesterases, acetylcholinesterase and heat shock protein 70 from larva brain tissue served as molecular parameters of sensitivity to benzo[a]pyrene presence. Carboxylesterases and Hsp70 were sensitive to low benzo[a]pyrene concentrations and population pre-exposure history, with a dependent response recorded. Different pollution biomarkers are suitable for different Lymantria dispar populations. Abstract: Plant vegetation accumulates polycyclic aromatic hydrocarbons (PAHs) among which benzo[a]pyrene (B[a]P) is recognized as being very toxic, including cancerogenic. Lymantria dispar L. larvae are sensitive to changes in the environment, providing potential signs of pollutant presence. We examined the chronic effects of two concentrations of B[a]P on the activity of carboxylesterase (CaE), acetylcholinesterase (AChE) and heat shock protein 70 (Hsp70) levels in the brain tissue of two populations of L. dispar larvae, originating from unpolluted and polluted habitats. We found that the relative growth rate was significantly lower in both populations and that only larvae from polluted forests were sensitive to low B[a]P concentrations, exhibiting a significant increase in brain tissue CaE activity and Hsp70 concentration. AChE activity showed no changes in response to B[a]P exposure in either population. Examined biochemical parameters indicate that their sensitivity to chronic treatment with B[a]P was highly dependent on the pre-exposure history of L. dispar larvae, suggesting that they could be promising biomarkers of B[a]P and PAH pollution in forest ecosystems. https://doi.org/10.2298/ABS190620056G Received: June 20, 2019; Revised: July 30, 2019; Accepted: August 28, 2019; Published online: September 6, 2019 How to cite this article: Grčić A, Ilijin L, Mrdaković M, Vlahović M, Filipović A, Đurašević S, Perić-Mataruga V. Benzo[a]pyrene-induced changes in carboxylesterase, acetylcholinesterase and heat shock protein 70 of Lymantria dispar (Lepidoptera: Lymantriidae) from unpolluted and polluted forests. Arch Biol Sci. 2019;71(4):735-45.